Data Integration in the Life Sciences 11th International Conference, DILS 2015, Los Angeles, CA, USA, July 9-10, 2015, Proceedings - Ashish, Naveen; Ambite, Jose-Luis (Lecture Notes in Bioinformatics,, 2015)
This book constitutes the proceedings of the 11th International Conference on Data Integration in the Life Sciences, DILS 2015, held in Los Angeles, CA, USA, in July 2015. The 24 papers presented in this volume were carefully reviewed and selected from 40 submissions. They are organized in topical sections named: data integration technologies; ontology and knowledge engineering for data integration; biomedical data standards and coding; medical research applications; and graduate student consortium.